MONITORING OF HEAVY METAL RESIDUES, METAL-METAL INTERACTIONS AND THE EFFECT OF COOKING ON THE METAL LOAD IN SHELLFISH - A. S. Atia; W. S. Darwish; M. S. Zaki (Journal of Animal and Plant Sciences, 2018)
Heavy metal pollution is considered a major problem worldwide. Heavy metals find their way to human body mainly through diet, water and air. Shellfish represents a major source of animal-derived protein, vitamins and trace elements; however, it may contribute to human exposure to heavy metals. This study was undertaken to monitor the toxic metal ( lead, cadmium, mercury and arsenic) residues in six shellfish namely, shrimp, crab, crayfish, clam, oyster and mussel collected from fish markets in Ismailia governorate, Egypt. Moreover, metal-metal interactions were also analyzed. Furthermore, human health risk assessment was estimated. Finally, the effect of different cooking methods on the toxic metal load in the shrimp was investigated. The results declared a clear and significant variation in the accumulation pattern of each metal in the examined shellfish. Positive correlations in the accumulation pattern of some metals were also observed in this study. High and continuous dietary intake of shellfish may constitute health hazards among consumers. Grilling and barbecuing of shellfish lead to an increase in the concentrations of toxic metals. However, boiling and frying significantly reduced the metal load in the shellfish. Public health implications of the examined metals were also discussed. metals are potent carcinogenic and mutagenic substances.
Keywords: Heavy metals; shellfish; cooking; health risk.